Vascularization of Air Sinuses and Fat Bodies in the Head of the Bottlenose Dolphin (Tursiops truncatus): Morphological Implications on Physiology - Costidis, Alex; Rommel, Sentiel A. (Frontiers in Physiology, 2012)
Cetaceans have long been considered capable of limiting diving-induced nitrogen absorption and subsequent decompression sickness through a series of behavioral, anatomical, and physiological adaptations. Recent studies however suggest that in some situations these adaptive mechanisms might be overcome, resulting in lethal and sublethal injuries. Perhaps most relevant to this discussion is the finding of intravascular gas and fat emboli in mass-stranded beaked whales. Although the source of the gas emboli has as yet to been ascertained, preliminary findings suggest nitrogen is the primary component. Since nitrogen gas embolus formation in divers is linked to nitrogen saturation, it seems premature to dismiss similar pathogenic mechanisms in breath-hold diving cetaceans. Due to the various anatomical adaptations in cetacean lungs, the pulmonary system is thought of as an unlikely site of significant nitrogen absorption. The accessory sinus system on the ventral head of odontocete cetaceans contains a sizeable volume of air that is exposed to the changing hydrostatic pressures during a dive, and is intimately associated with vasculature potentially capable of absorbing nitrogen through its walls. The source of the fat emboli has also remained elusive. Most mammalian fat deposits are considered poorly vascularized and therefore unlikely sites of intravascular introduction of lipid, although cetacean blubber may not be as poorly vascularized as previously thought. We present new data on the vasculature of air sinuses and acoustic fat bodies in the head of bottlenose dolphins and compare it to published accounts. We show that the mandibular fat bodies and accessory sinus system are associated with extensive venous plexuses and suggest potential physiological and pathological implications.